2022
DOI: 10.1136/bmjopen-2021-052920
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers for the implementation of exercise are medicine in routine clinical care in Dutch university medical centres: a mixed methodology study on clinicians’ perceptions

Abstract: ObjectivesDespite the many proven advantages of a physically active lifestyle in patient populations, prescription of exercise is currently not widely implemented in routine clinical practice. The aims of this study were twofold: (1) to assess perceptions of clinicians on the current practice of exercise is medicine (E=M) prescription in two Dutch university medical centres and (2) to determine their perceived barriers and facilitators for the implementation of E=M in routine clinical care in Dutch university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(52 reference statements)
4
3
0
1
Order By: Relevance
“…The most common reason for not prescribing PA was forgetting, followed by a lack of knowledge about current PA prescribing recommendations and lack of time. Our ndings on barriers to PA prescribing are consistent with those of other authors (41)(42)(43)(44)(45)(46)(47). Nauta et al (47) identi ed forgetting as a major reason for not prescribing PA. Persson et al (49) highlighted the current recommendations' ignorance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common reason for not prescribing PA was forgetting, followed by a lack of knowledge about current PA prescribing recommendations and lack of time. Our ndings on barriers to PA prescribing are consistent with those of other authors (41)(42)(43)(44)(45)(46)(47). Nauta et al (47) identi ed forgetting as a major reason for not prescribing PA. Persson et al (49) highlighted the current recommendations' ignorance.…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings on barriers to PA prescribing are consistent with those of other authors (41)(42)(43)(44)(45)(46)(47). Nauta et al (47) identi ed forgetting as a major reason for not prescribing PA. Persson et al (49) highlighted the current recommendations' ignorance. Similarly, other previous studies have been identi ed a lack of time as a barrier to prescribing daily PA (41,44,45).…”
Section: Discussionsupporting
confidence: 92%
“…The E = M tool may also be used for ongoing monitoring during treatment. In our interrelated study it was already indicated by clinicians that continuous monitoring of PA behavior is recommended [ 28 ]; If the PA behavior decreases considerably, this may be a sign that the patient is not doing well. When such a tool is used to set up a tailored training program or to measure effects of a medical treatment, PA measurement should include intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to the implementation and uptake of exercise prescription include; lack of time, insufficient skills to address patients’ PA behavior, insufficient knowledge of PA guidelines and referral options and subjective influences as immediate and significant barrier to this referral process [ 26 31 ]. Strategies to overcome these barriers should focus on increasing clinicians EIM referral skills, improving clinicians knowledge of EIM referral options and develop a support system to ensure that EIM is high on the priority list of clinicians [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation